Prevalence of contact allergy to corticosteroids in a Danish patient population. (26th May 2022) - Svendsen, Sebastian Vigand; Bach, Rasmus Overgaard; Mortz, Charlotte G.
Abstract: Background: Allergic contact dermatitis to corticosteroids can be a challenging diagnosis as corticosteroids are used in the treatment of dermatitis. The prevalence of contact allergy to corticosteroid varies between previous studies. Objective: To study the prevalence of sensitization to budesonide, tixocortol‐21‐pivalate and hydrocortisone‐17‐butyrate in a Danish patient population from 2006‐2020, cross‐sensitization, risk factors and clinical relevance. Methods: A retrospective analysis of patch test data and MOAHLFA index was performed among 6823 patients consecutively patch tested with TRUE test as part of the baseline series. Results: A positive patch test for corticosteroids was found in 185 patients (1.2% budesonide, 1.6% tixocortol‐21‐pivalate, 1.0% hydrocortisone‐17‐butyrate) without gender difference. For women, the prevalence of tixocortol‐21‐pivalate sensitization increased significantly from 1.3% in 2006–2008 to 2.9% in 2018–2020. Tixocortol‐21‐pivalate sensitization had more frequently clinical relevance in women (61.3%) compared to men (34.5%). Age above 40 years was positively associated to corticosteroid sensitization. Budesonide and hydrocortisone‐17‐butyrate accounted for 67.7% of co‐sensitizations. Conclusions: The prevalence of corticosteroid sensitization was 2.7%. Age was the only risk factor for corticosteroid sensitization. The frequency of corticosteroid sensitization was stabile over time except for tixocortol‐21‐pivalate sensitization for women. About one third of sensitized patients had co‐sensitizations to other corticosteroid groups. Abstract : Of 6823 consecutively patch tested patients, 2.7% ( n = 185) were sensitized to corticosteroid markers (budesonide, tixocortol‐21‐pivalate, hydrocortisone‐17‐butyrate). Tixocortol‐21‐pivalate sensitization in women increased significantly from 1.3% in 2006–2008 to 2.9% in 2018–2020. Age above 40 years was associated with higher prevalence of corticosteroid sensitization.